THE FATIGUE CUMULATIVE DAMAGE PROBABILITY MODEL OF GEAR CONTACT - LV YuanBo; ZHUO Yi; ZHANG WenDong (Jixie qiangdu)
For the gear transmission mechanism of a slat,based on S-N curve and linear cumulative damage theory,the reliability fatigue life caculation formula of gear contact can be obtained.In order to realize the global influence of the basic random variables on the distribution of the response performance function completely,the global sensitivities are proposed,which can provide effective theoretical guidance for optimazation and reliability design of gear.